(untitled) (Imaginations: Journal of Cross-Cultural Image Studies, 2016)
Abstract | The text-essay by Karen Engle, “Fragments of Desire,” and photo-essay by Trudi Lynn Smith, “Finding Aid: NxW,” together form a conversation intended to explore connections between photography, truth, impossibility, and failure within photography in present-day Waterton Lakes National Park, Canada. In response to the provocation of this special issue, Smith selected pieces from her archival artwork Finding Aid and mailed it to Engle, who wrote the essay in response to her encounter with the archive. When Smith received the essay, she created a photo-essay from the archive in response to Engle’s text. Résumé | L’essai de Karen Engle « Fragments de désir » et le reportage photo de Trudi Lynn Smith forment une conversation ayant pour but d’explorer la connexion entre photographie, vérité, impossible et échec dans la photographie contemporaine du parc national Waterton Lakes. En réponse au défi posé par cette édition spéciale, Smith a sélectionné des images de son œuvre archivistique Finding aid puis les a envoyées à Engle qui a écrit son essai à partir de son interaction avec ces documents d’archives. Suite à la réception de l’essai, Smith a créé le reportage photo à partir des archives en réponse au texte d’Engle.